Stochastic Production Frontier Models to Explore Constraints on Household Travel Expenditures Considering Household Income Classes - Sofyan M. Saleh; Sugiarto Sugiarto (Aceh International Journal of Science and Technology, 2016)
This paper explores the variation of household travel expenditure frontiers (HTEFs) prior to CC reform in Jakarta. This study incorporates the variation of household income classes into the modeling of HTEFs and investigates the degree to which various determinants influence levels of HTEF. The HTEF is defined as an unseen maximum (capacity) amount of money that a certain income class is willing to dedicate to their travel. A stochastic production frontier is applied to model and explore upper bound household travel expenditure (HTE). Using a comprehensive household travel survey (HTS) in Jakarta in 2004, the observed HTE spending in a month is treated as an exogenous variable. The estimation results obtained using three proposed models, for low, medium and high income classes, show that HTEFs are significantly associated with life stage structure attributes, socio-demographics and life environment factors such as professional activity engagements, which is disclosed to be varied across income classes. Finding further reveals that considerable differences in average of HTEFs across models. This finding calls for the formulation of policies that consider the needs to be addressed for low and medium income groups in order to promote more equity policy thereby leading to more acceptable CC reform.